COPYRIGHT GOSSIP: EXPLORING COPYRIGHT KNOWLEDGE, SENTIMENT AND BLACKBOX THEORIES ON YOUTUBE - Kaye, D. Bondy Valdovinos; Gray, Joanne E (AoIR Selected Papers of Internet Research, 2020)
This study investigates copyright discourses on YouTube. Through a qualitative content analysis of approximately 200 YouTube videos, we explore how YouTube creators understand copyright law, and how they navigate a highly technical and dynamic copyright enforcement ecosystem. Our findings offer insights into how digitally situated cultural producers are impacted by and respond to automated content moderation. This is important because increasingly lawmakers around the world are asking digital platforms to implement efficient systems for content moderation and yet there is a lack of good information about the stakeholders most directly impacted by these practices. In this study, we provide a systematic analysis of the opinions and strategies of creators who are affected by YouTube’s copyright enforcement measures.